1976
DOI: 10.1530/acta.0.0820426
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Mechanisms Involved in the Control of Oestrous Cycle Duration by the Odour of Urine in the Rat

Abstract: The mechanisms involved in the reduced cycle duration following exposure to the odour of urine were studied in natural and experimental 5-day cyclic female Wistar rats.A decrease in the rate of ovarian progesterone secretion from the morning of dioestrus I to that of dioestrus II was observed in females whose cycle duration was reduced from 5 to 4 days following exposure to the odour of rat urine. No decrease in ovarian progesterone secretion occurred in females maintaining a 5-day cyclicity despite exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In female rats, pheromones in urine excreted from males and females induce various changes in gonadal functions, including reflex ovulation in the absence of coitus and mounting ( Johns et al . 1978 ), a reduction in the oestrous cycle of female rats from 5 to 4 days ( Chateau et al . 1976 ), and restoration of the oestrous cycle that has been inhibited by treatment with oestradiol ( Mora & Cabrera 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In female rats, pheromones in urine excreted from males and females induce various changes in gonadal functions, including reflex ovulation in the absence of coitus and mounting ( Johns et al . 1978 ), a reduction in the oestrous cycle of female rats from 5 to 4 days ( Chateau et al . 1976 ), and restoration of the oestrous cycle that has been inhibited by treatment with oestradiol ( Mora & Cabrera 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The pregnancy block has not been observed in rats. In rats, pheromones in the urine of males reduced the oestrous cycle of females from 5 to 4 d 2) and induced the dioestrous stage and restored oestrous cycles in irregularly cycling and anovulatory persistent-oestrous aging females. 21) Baseline plasma progesterone concentrations in irregularly cycling and anovulatory-oestrous females were similar to those in normally cycling 7-8-month-old females; male urinary pheromones increased the levels of plasma progesterone in these females.…”
Section: Discussionmentioning
confidence: 98%
“…Pheromones have been found in saliva, skin gland secretions, and urine. For example, pheromones in the urine excreted from male and female rats induce various changes in gonadal function and endocrine state, including reflex ovulation in the absence of coitus and mounting, 1) and a reduction in the oestrous cycle of female rats from 5 to 4 d, 2) and oestrous synchrony among female rats housed together.3) The vomeronasal organ exists in many vertebrates for the purpose of receiving pheromones, which in turn affect sexual and social behavior. 4,5) In a previous study, we demonstrated that the sensory neurons in the vomeronasal organ (VNO) of female rats, which respond to male Wistar urine, are localized in the apical layer of the epithelium, where one type of G i2a is selectively expressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pheromones have been found in saliva, skin gland secretions, and urine. For example, pheromones in the urine excreted from male and female rats induce various changes in gonadal function and endocrine state, including reflex ovulation in the absence of coitus and mounting, 15) and a reduction in the oestrous cycle of female rats from 5 to 4 d, 16) and oestrous synchrony among female rats housed together.17) The VNO exists in many vertebrates for the purpose of receiving pheromones, which in turn affect sexual and social behavior. 18,19) Vomeronasal sensory neurons project to the AOB located on the dorso-caudal surface of the MOB.…”
mentioning
confidence: 99%